Предмет: Математика,
автор: voronenokgameower
5(6х-1)=3х-5
2х-5=7(3х+4)+5
СРОЧНО
Ответы
Автор ответа:
1
1.5(6х-1)=3х-5
30х-5=3х-5
30х-3х=5-5
27х=0
х=0:27
х=0
2.2х-5=7(3х+4)+5
2х-5=21х+28+5
2х-21х=5+28+5
-19х=38
х=38:(-19)
х=-2
voronenokgameower:
спасибоо
Автор ответа:
0
5(6х - 1) = 3х - 5
30х - 5 = 3х - 5
30х - 3х = 5 - 5
27х = 0
х = 0 : 27
х = 0 - корень уравнения
Проверка: 5 · (6 · 0 - 1) = 3 · 0 - 5
5 · (-1) = 0 - 5
-5 = -5 - верно.
- - - - - - - - - - - - - - - - - - - - - -
2х - 5 = 7(3х + 4) + 5
2х - 5 = 21х + 28 + 5
2х - 21х = 28 + 5 + 5
-19х = 38
х = 38 : (-19)
х = -2 - корень уравнения
Проверка: 2 · (-2) - 5 = 7 · (3 · (-2) + 4) + 5
-4 - 5 = 7 · (-2) + 5
-9 = -14 + 5
-9 = -9 - верно.
Похожие вопросы
Предмет: Русский язык,
автор: PereverzevaoL
Предмет: Русский язык,
автор: РейханАгамирли
Предмет: Немецкий язык,
автор: snizhana29
Предмет: Биология,
автор: sveta9649
Предмет: Информатика,
автор: bass33615